Charge Balance and Exciton Confinement in Phosphorescent Organic Light Emitting Diodes. Issue 6 (17th March 2016) - Coburn, Caleb; Lee, Jaesang; Forrest, Stephen R.
Abstract : Thin red "sensing layers" are used to measure exciton confinement and charge balance in blue phosphorescent light emitting diodes. The device stability and efficiency are improved by preventing triplet exciton leakage from the emission zone. The results are explained using a quantitative model for charge and exciton transport.